Income-related health inequality among rural residents in western China - Li, Chaofan; Tang, Chengxiang (Frontiers in Public Health, 2022)
Objective Health equality has drawn much public attention in both developed and developing countries. China, the largest developing country, has implemented a new round of health system reform to improve health equality since 2009. This study aims to examine the magnitude and sources of income-related health inequality in western rural regions of China. Methods Data were obtained from the Survey of Rural Economic and Social Development in Western China conducted in 2014, in which 14,555 individuals from 5,299 households in 12 provinces were included. Health outcome variables of interest were self-rated health status, prevalence of chronic disease and four-week illness. Concentration index was calculated to assess magnitude of income-related health inequality, and nonlinear decomposition analysis was performed to identify the sources of health inequality. Results The Concentration indexes for poor self-rated health status, prevalence of chronic disease and four-week illness were −0.0898 (P<0.001),−0.0860 (P<0.001) and −0.1284 (P<0.001), respectively. Income and education were two main sources of health inequality, accounting for about 25−50% and 15% contribution to the inequality. Ethnicity made <10% contribution to income-related health inequality, and enrollment in New Rural Cooperative Medical Scheme contributed to <1%. Conclusion This study found slight income-related health inequality among rural residents in western China, implying that although China has made substantial progress in economic development and poverty alleviation, health inequality in western rural region should still be concerned by the government. To achieve health equality further, the Chinese government should not only strengthen its reimbursement mechanism of the current health insurance scheme to improve affordability of primary healthcare for residents in western rural regions, but also implement health poverty alleviation policies targeting socioeconomically vulnerable population and ethnic minorities in future.